PERFORMA AYAM PEDAGING PADA SISTEM BROODING KONVENSIONAL DAN THERMOS - Fatmaningsih, Rani; Riyanti, Rr.; Nova, Khaira (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to determine the best performance of broiler in the conventional brooding system and the thermos.Â  The research was conducted from December 4, 2015 - January 3, 2016 , in the Experiment Farm PT Ramajaya. MaterialÂ  research is a broiler strain new lohmann aged 0 --14 days as many as 2000 individuals. Experiments based on case studies. The study used two experimental brooding systems, namely P1 : Conventional brooding system; P2 : Thermos brooding system. The results showed that the performance of ayam pedaging in thermos brooding system such as feed intake, body weight and feed conversion is better than the performance of the conventional brooding system . Keywords : Broiler, Brooding Systems, Performance